Penerapan Strategi Mnemonic Akronim dalam Pembelajaran Akidah Akhlak pada Kelas XII IPK di MAN 2 Pesisir Selatan - Rengga Satria; Hidayatul Rahmi (AS-SABIQUN, 2022)
This study aims to determine how the planning, implementation and evaluation of the aplication of the acroniym mnemonic strategy in MAN 2 Pesisir Selatan. This research is a field research with a qualitative approach, the data sources are taken from several informants using purposive sampling. The outhor uses is data collection, data reduction, data presentation and conclusion drawing. The results of this study indicate: First, planning including, preparation before learning the teacher prepares lesson plans, concept maps, prepares materials and teaching materials. Preparations before studying such as conditioning the study room free from garbage and saying greetings. Seconds, the implementation consists of introduction such as reading prayers before studying, taking student attendance. Core activities such as introducing value banks, reviewing material, giving motivation to students and closing, the teacher presents sub materals at the next meeting. Third, the evaluation of this activity is that the teacher calls studts to come to the front of the class and repeat the material that has been taught by the teacher in an oral test.